Community-Associated Methicillin-Resistant Staphylococcus aureus in a Pediatric Emergency Department in Newfoundland and Labrador - Erin Peebles; Robert Morris; Roger Chafe (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: First-generation cephalosporins and antistaphylococcal penicillins are typically the first choice for treating skin and soft tissue infections (SSTI), but are not effective for infections caused by methicillin-resistant Staphylococcus aureus (MRSA). It is currently unclear what percentage of SSTIs is caused by community-associated MRSA in different regions in Canada.